Unaccompanied Afghan children: on the move again? - Shahab, S (Refugee Studies Centre, University of Oxford, 2014)
Many Afghan minors who previously left Afghanistan for the West but were forcibly returned are keen to set out again, despite the challenges faced during their journeys